2016
DOI: 10.18632/oncotarget.9224
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid stimulates epithelial to mesenchymal transition marker Slug/Snail2 in ovarian cancer cells via Gαi2, Src, and HIF1α signaling nexus

Abstract: Recent studies have identified a critical role for lysophosphatidic acid (LPA) in the progression of ovarian cancer. Using a transcription factor activation reporter array, which analyzes 45 distinct transcription factors, it has been observed that LPA observed robustly activates the transcription factor hypoxia-induced factor-1α (HIF1α) in SKOV3.ip ovarian cancer cells. HIF1α showed 150-fold increase in its activation profile compared to the untreated control. Validation of the array analysis indicated that L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 70 publications
3
52
0
Order By: Relevance
“…Thus, our data suggest that LPA induces EMT and invasion in OC cells by suppressing SIRT1 expression. According to the previous reports and our unpublished data, LPA induces the expression of HIF1α promoting invasion in OC cells [44-46]. From our data, it can be suggested that LPA-mediated SIRT1 down-regulation helps in the maintenance of the acetylated and functional form of HIF1α thereby, triggering cancer invasion.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, our data suggest that LPA induces EMT and invasion in OC cells by suppressing SIRT1 expression. According to the previous reports and our unpublished data, LPA induces the expression of HIF1α promoting invasion in OC cells [44-46]. From our data, it can be suggested that LPA-mediated SIRT1 down-regulation helps in the maintenance of the acetylated and functional form of HIF1α thereby, triggering cancer invasion.…”
Section: Discussionsupporting
confidence: 76%
“…Immunoblot analysis for JNK, pJNK, JLP, GAPDH, and with the indicated antibodies were carried out following previously published procedures [47, 51, 52] and developed with a Kodak Image Station 4000 MM.…”
Section: Methodsmentioning
confidence: 99%
“…Epithelial to mesenchymal transition (EMT), a reversible biological process, is characterized by the loss of epithelial cell junction proteins (E-cadherin, Zo-1) (7,8), the gain of mesenchymal markers (vimentin, N-cadherin) (9,10), and the activation of transcription factors (Snail1, Slug, ZEB1, Twist) (11)(12)(13)(14)(15). Accumulating evidence indicates that EMT enhances tumor invasion, distant metastasis, and chemotherapy resistance in NSCLC, underscoring the need for a comprehensive understanding of the EMT function in NSCLC progression (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%